G‐Protein‐Coupled Receptor 84 Aggravates Early Brain Injury via Microglial NLRP3‐ASC Inflammasome After Subarachnoid Hemorrhage - Kun Jiang; Yan Zou; Yue Song; Long'jiang Zhou; Bing'tao Zhang; Xiao'ming Zhou; Xin Zhang (Brain and Behavior)
ABSTRACT Background Subarachnoid hemorrhage (SAH) is one of the most devastating hemorrhagic strokes. SAH causes neuroinflammation and leads to both early brain injury and delayed brain injury. G‐protein‐coupled receptor 84 (GPR84), one of the orphan class‐A G protein‐coupled receptors (GPCRs), exerts pro‐inflammatory and pro‐phagocytic effects via targeting microglia in the central nervous system (CNS). This research investigated the role of GPR84 on SAH pathology via neuroinflammation. Methods An enzyme‐linked immunosorbent assay was used for GPR84 expression in cerebrospinal fluid (CSF) samples from patients with SAH. An experimental SAH‐model mouse was established by stereotactic injection of autologous blood into the chiasmatic cisterna. The SAH model in vitro was established by exposing microglia to hemoglobin. After inhibition of GPR84 in mice by GPR84‐siRNA and GPR84‐antagonist 3, the neurological deficits were evaluated by modified Garcia test, beam balance test, and Morris water maze. Neuronal death in SAH‐model mice was evaluated by Nissl staining. GPR84, NLRP3 inflammasome, and cAMP/PKA expressions were detected by western blot and immunofluorescence. Results GPR84 was upregulated in patients after SAH onset. The GPR84 expression in microglia increased after SAH onset, activated NLRP3 inflammasome, and promoted IL‐1β secretion. Both GPR84‐shRNA and GPR84‐antagonist 3 improved neurological deficits in SAH‐model mice. Mechanistically, GPR84 activated the NLRP3 inflammasome via the cAMP/PKA signaling pathway to aggravate neuronal injury. Conclusions GPR84 promotes NLRP3‐mediated pyroptosis and activated NLRP3 inflammation via cAMP/PKA pathway.